Auction versus direct sale: the effect of buyers and sellers on prices. (10th November 2022) - Sogn-Grundvåg, Geir; Zhang, Dengjun
Abstract: This study examines the question of selling agricultural commodities by auction or directly. Hedonic price analysis using transaction data from the sale of frozen cod in Norway shows that buyer–seller matches explain 32.4 and 13.6 per cent of the price variation in direct sales and auctions, respectively, indicating that direct sales are more informationally efficient than auctions. Meanwhile, auctions gain a price premium of 2.6 per cent over direct sales, holding other variables constant. However, a substantial increase in the use of direct sales indicates that their information efficiency is more important to sellers than the small price premium provided by auctions.